2014
DOI: 10.1111/cdev.12334
|View full text |Cite
|
Sign up to set email alerts
|

Children Use Nonverbal Cues to Make Inferences About Social Power

Abstract: Four studies (N=192) tested whether young children use nonverbal information to make inferences about differences in social power. Five- and 6-year-old children were able to determine which of two adults was “in charge” in dynamic videotaped conversations (Study 1) and in static photographs (Study 4) using only nonverbal cues. Younger children (3–4 years) were not successful in Study 1 or Study 4. Removing irrelevant linguistic information from conversations did not improve the performance of 3–4-year-old chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 39 publications
9
127
0
Order By: Relevance
“…Previous research in other areas has shown that girls are more able to use subtle social cues to make inferences about others" behavior (e.g., Brey & Shutts, 2015;Hall, 1978). Consistent with this idea, in the current study, girls…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous research in other areas has shown that girls are more able to use subtle social cues to make inferences about others" behavior (e.g., Brey & Shutts, 2015;Hall, 1978). Consistent with this idea, in the current study, girls…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, they are sensitive to subtle differences in other social cues (Brey & Shutts, 2015;Over & Carpenter, 2015), and are able to differentiate real from pretend emotions (Gross & Harris, 1988;Harris et al, 1986;Misailidi, 2006;Mizokawa, 2011). Furthermore, around this age, children are developing an understanding of the psychological states underlying others" behavior -their "theory of mind" (e.g., Wellman, Cross, & Watson, 2001).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This is in line with findings that effects typical for concrete magnitudes replicate for power as well (Chiao, 2010), and that already preverbal infants expect larger agents to prevail in zero-sum conflicts (Thomsen, Frankenhuis, Ingold-Smith, & Carey, 2011). Brey and Shutts (2015) observed that 5-year-old preschool children were sensitive to vertical spatial information inherent in postures when judging social power of people:…”
Section: Development Of the Space-power Associationsupporting
confidence: 89%
“…Furthermore, eye-movement studies (Mascaro & Csibra, 2012;Thomsen et al, 2011) showed that even infants were sensitive to the power of two agents; 4) Are children's spatial representations of power too different from that of adults? Again, the results from both Experiment 1 and Brey and Shutts (2015) showed that children had developed the same relation between power and space as adults (powerful = up, powerless = down). Instead, the null result seems to be related to the fact that children do not automatically activate the power concept or its related spatial representation.…”
Section: Discussionmentioning
confidence: 80%
“…Additional children participated, but were excluded from analyses due to experimenter error ( N = 1) or not finishing the session ( N = 4). We predetermined a stopping rule of 32 participants per condition based on previous studies examining children’s understanding of nonverbal behaviors (Brey & Shutts, 2015). …”
Section: Methodsmentioning
confidence: 99%